GLP-1 and Underlying Beneficial Actions in Alzheimer’s Disease, Hypertension, and NASH - Li, Qiu-Xuan; Gao, Han; Guo, Yue-Xin; Wang, Bo-Ya; Hua, Rong-xuan; Gao, Lei; Shang, Hong-Wei; Lu, Xin; Xu, Jing-Dong (Frontiers in Endocrinology, 2021)
GLP-1 is derived from intestinal L cells, which takes effect through binding to GLP-1R and is inactivated by the enzyme dipeptidyl peptidase-4 (DPP-4). Since its discovery, GLP-1 has emerged as an incretin hormone for its facilitation in insulin release and reduction of insulin resistance (IR). However, GLP-1 possesses broader pharmacological effects including anti-inflammation, neuro-protection, regulating blood pressure (BP), and reducing lipotoxicity. These effects are interconnected to the physiological and pathological processes of Alzheimer’s disease (AD), hypertension, and non-alcoholic steatohepatitis (NASH). Currently, the underlying mechanism of these effects is still not fully illustrated and a better understanding of them may help identify promising therapeutic targets of AD, hypertension, and NASH. Therefore, we focus on the biological characteristics of GLP-1, render an overview of the mechanism of GLP-1 effects in diseases, and investigate the potential of GLP-1 analogues for the treatment of related diseases in this review.